The Fourier transforms of Lipschitz functions on the Heisenberg group - M. S. Younis (International Journal of Mathematics and Mathematical Sciences, 2000)
We study the order of magnitude of the Fourier transforms of certain Lipschitz functions on the Heisenberg group Hn. We compare our conclusions with some previous results in the field.